Le emergenze umanitarie complesse Un'introduzione - Bellanca, Nicolo' (Strumenti per la didattica e la ricerca, 2005)
The main contemporary crisis situations concern ecology, public health, markets, technology and war. They now manifest themselves not simply as sectoral crisis (of the economy, finance, environment, and so on), but as complex humanitarian emergencies. This volume examines these issues from the perspective of two theoretical categories: that of tragic choices (which escape the negotiation logic of the more-or-less, tending to the violent logic of all-or-nothing) and that of global collective action (which aims to build or safeguard non-excludable goods that cross borders and generations). The goal is to make the reader think about the multiple but complementary ways in which these emergencies can be faced "by transforming the terms of the tragic choices and encouraging the emergence of global collective actions".